2009
DOI: 10.1017/s0007114509993059
|View full text |Cite
|
Sign up to set email alerts
|

Is undernutrition a risk factor for sensorineural hearing loss in early infancy?

Abstract: The present cross-sectional study set out to determine the nutritional status of infants aged 0 -3 months with the WHO Multicentre Growth Reference (WHO-MGR) and examine the relationship between undernutrition and congenital or early-onset sensorineural hearing loss (CESHL) rarely reported for developing countries. The nutritional status of all infants attending community-based clinics for routine Bacille de Calmette-Guérin (BCG) immunisation from July 2005 to December 2006 was determined by weight-for-age, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The effect of malnutrition on hearing and language, as observed in this study, has also been observed in other studies. [20][21][22] Previous studies [20][21][22] have shown that malnutrition causes delay in maturation of the auditory pathway and also affects both central and peripheral hearing. Nutritional deficiencies, even in acute form, impair the normal functioning of the middle ear, with negative consequences for the entire auditory system.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of malnutrition on hearing and language, as observed in this study, has also been observed in other studies. [20][21][22] Previous studies [20][21][22] have shown that malnutrition causes delay in maturation of the auditory pathway and also affects both central and peripheral hearing. Nutritional deficiencies, even in acute form, impair the normal functioning of the middle ear, with negative consequences for the entire auditory system.…”
Section: Resultsmentioning
confidence: 99%
“…Infants with any undernourished physical state were significantly more likely to have severe-profound sensori-neural hearing loss than infants without any undernourishment. 17 The second publication built upon these results and added weight-for-length as a fourth index. It also encompassed a larger total study population (n = 6585) and also demonstrated that early-onset permanent hearing loss was significantly more prevalent among undernourished infants.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses by mean body indices may be more widely applicable, since sex-specific z -scores for nutritional indices were obtained from the World Health Organization Multicentre Growth references. 17,18,38 …”
Section: Discussionmentioning
confidence: 99%
“…Nutrient needs tend to lie in parallel rates of children growth. Olusanya [2] noted that growth continues at a steady rate during childhood then, accelerates during adolescence, creating increases in nutrient needs to support the rapid growth rate and increase in lean body mass and body size. The nutrient requirements among individuals differ with age, gender, body size and physiological state.…”
Section: Introduction mentioning
confidence: 99%
“…Although the focus of concern for children with disability is generally around under-nutrition, becoming overweight is also a concern for some disabled children. For example, children with certain physical disabilities are less mobile and therefore at risk of becoming overweight [2]. Other children with certain types of genetic impairments (e.g., Sotos syndrome) or intellectual or mental health disabilities may have eating disorders which place them at greater risk of becoming overweight.…”
Section: Introduction mentioning
confidence: 99%